Design, Production Cost, and Air Flow Distribution of Biomass Pellet Furnace - Heru Sutanto; Suyitno Suyitno; Wibawa Endra Juwana; Tito Gusti Nurrohim (Mekanika: Majalah Ilmiah Mekanika, 2021)
Biomass attracts a great deal of attention because it is converted into green fuels in the form of pellets. The furnace is needed to burn pellets to generate up to 300 kW of heat. In addition to meeting the heat capacity needs of small and medium-sized industries, furnaces must also be competitive in terms of price. Therefore, the purpose of this study is to obtain details of the cost of manufacturing the furnace and the airflow model that occurs in the furnace. This study employs a forward and reverses engineering approach, beginning with determining load and capacity, drawing, determining the bill of materials and manufacturing, numerical modeling of airflow with ANSYS FLUENT, fabrication, and final testing. The outcome revealed that the furnace's production cost included manufacturing costs, assembly costs, machining, and repair costs. The findings revealed that the critical portion of the cost of the furnace was the material cost of 77%. The simulation findings showed that the total pressure difference of up to 850 Pa had to be resolved by air-supplying blowers. The gas velocity ranged from 2 to 10 m/s and increased significantly near the exit to 42 m/s.